2006
DOI: 10.1055/s-2006-949668
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis and Classification of von Willebrand Factor/Factor VIII Concentrates: Impact on Treatment of Patients with von Willebrand Disease

Abstract: von Willebrand disease (vWD) is a bleeding disorder that results from defects in the quality or quantity of von Willebrand factor (vWF), a glycoprotein essential for normal thrombus formation. vWF circulates in plasma as multimers in sizes ranging up to 20,000 kd. The high molecular weight vWF (HMWvWF) multimers are most essential for primary hemostasis, whereas the lower molecular weight multimers are less functionally active. For many patients, the treatment of choice is factor replacement with a vWF/FVIII c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 19 publications
4
72
0
4
Order By: Relevance
“…Our novel clinical data, taken together with previously published experimental evidence, suggest a possible pathophysiological role for vWF: i.e. the increased presence of the more functionally active HMW-vWF multimers [5] with potential pro-coagulant and pro-adhesive effects. They thus provide a basis for further examination of hypoxemia-driven vWF-mediated pathophysiology in SCD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our novel clinical data, taken together with previously published experimental evidence, suggest a possible pathophysiological role for vWF: i.e. the increased presence of the more functionally active HMW-vWF multimers [5] with potential pro-coagulant and pro-adhesive effects. They thus provide a basis for further examination of hypoxemia-driven vWF-mediated pathophysiology in SCD.…”
Section: Discussionsupporting
confidence: 63%
“…In vitro studies have shown that hypoxia is a strong agonist for endothelial release of von Willebrand factor (vWF) [3] including ultra large vWF (ULvWF) multimers [4]. vWF is a large multimeric glycoprotein critical for normal platelet function in primary hemostasis, its high molecular weight (HMW-vWF) multimers being the most hemostatically active subunits [5]. Sparse information is available regarding the relationship between vWF and clinical hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Plasma-derived VWF/FVIII products also vary in composition depending on the source plasma and the manufacturing process. [16][17][18][19] This variability could lead to excessive FVIII levels in VWD patients, with inherent risk of venous thromboembolism. Furthermore, these concentrates show variable deficiency of ultralarge multimers (ULM) of VWF due to proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…18 Plasmaderived VWF concentrates variably lack ULM due to in vivo exposure to plasma ADAMTS13 (a disintegrin and metalloprotease with a thrombospondin type 1 motif, member 13) and proteolytic cleavage by granulocyte elastases. [16][17][18][19] In contrast to VWF concentrates derived from plasma, rVWF has no exposure to the human protease ADAMTS13 during the production process and therefore contains intact HMWM and ULM. 22 The presence of ULM and the higher purity also contribute to a greater specific activity of rVWF measured as VWF:ristocetin cofactor activity (VWF:RCo) relative to VWF:antigen (VWF:Ag).…”
Section: Introductionmentioning
confidence: 99%
“…All but one of these products represent plasma-derived VWF-FVIII concentrates with various VWF:FVIII ratios and multimer profiles that show minor differences. 51 In the studies that have been published relating to the clinical efficacy and safety of these products, they all appear to provide satisfactory hemostasis and are not accompanied by serious adverse events. The use of VWF concentrates with very low FVIII content should be accompanied by the coinfusion of recombinant FVIII to enhance the treatment of acute bleeding episodes and to optimize surgical hemostasis.…”
Section: Advances In the Treatment Of Vwdmentioning
confidence: 99%